Pendampingan Suami Berpengaruh dalam Mengurangi Kecemasan Ibu Primigravida Kala I di PMB Pariawati - Fitria Fitria; Retno Wahyuni; Herna Rinayanti Manurung; Lidya Natalia Sinuhaji; Febriana Sari; Asnita Sinaga (Universitas Muhamadiyah Manado, 2022)
Childbirth is a physiological process experienced by mothers of childbearing age, giving birth to a baby is a process that is eagerly awaited by husband and wife couples, apart from that, when facing childbirth a mother will feel anxious and worried (I. Kuswanti & Melina, 2019a) Family health program recording at the Ministry of Health in 2020, the number of maternal deaths showed 4,627 deaths in Indonesia and this has increased compared to 2019 which was 4,221 deaths. , and seen based on the causes and the majority of them, there are 1,330 cases of bleeding, 1,110 cases of hypertension in pregnancy, and 230 cases of circulatory system disorders. The research that I have carried out is a type of Quantitative research. According to (Sujarweni, 2020) in the book Research Methodology defines quantitative research as a process of discovering knowledge that uses data in the form of numbers as a tool for analyzing information about what is known. In this research, the researcher used a questionnaire sheet. Based on the preliminary survey data that I had conducted at PMB Pariawati Tinggi Cliff, that there were mothers who were in labor who were anxious when they were about to give birth, the researcher was interested in taking the title of the effect of husband's assistance on reducing anxiety in the birth process of primigravida mothers in the first stage at PMB Pariawati Tebing Tinggi. And after I conducted research at PMB Pariawati Tebing Tinggi in 2022 which lasted around 3 months and I got 35 mothers who Primigravida who is about to give birth experiences anxiety.